Cost Variations In MDR-TB And XDR-TB Laboratory Examinations - Tri Mulyani (International Forum of Researchers and Lecturers, 2024)
Tuberculosis (TB) remains a significant global health concern, with Mycobacterium tuberculosis as the causative agent. The emergence of drug-resistant forms, such as Multi-drug-resistant TB (MDR-TB) and Extensive-drug-resistant TB (XDR-TB), poses substantial challenges in TB management. This study focuses on analyzing the cost variations associated with laboratory examinations for MDR-TB and XDR-TB patients undergoing treatment cycles at a tertiary hospital.The methodology involved the inclusion of patients diagnosed with MDR-TB or XDR-TB who underwent a range of laboratory tests during their treatment. A cross-sectional retrospective analytics approach was employed, utilizing medical records from the hospital's MDR division.The results of the study, encompassing 30 MDR-TB patients and 2 XDR-TB patients, revealed significant differences in laboratory examination costs between the MDR-TB and XDR-TB groups (p = 0.018). This disparity underscores the financial burden associated with managing drug-resistant TB variants, particularly in terms of laboratory monitoring and diagnostic procedures.The discussion delves into the implications of these cost variations, highlighting the challenges faced by healthcare systems and patients in resource allocation and financial planning for TB treatment. The findings underscore the importance of cost-effective strategies and optimized laboratory protocols to ensure comprehensive yet affordable care for MDR-TB and XDR-TB patients.In conclusion, this study sheds light on the considerable cost variations in laboratory examinations for MDR-TB and XDR-TB patients, emphasizing the need for efficient resource utilization and targeted interventions to address the financial aspects of managing drug-resistant TB strains effectively.